Core Competencies and Technological Skills of Maritime Professionals In the Fourth Industrial Revolution Towards a Strategic Plan - Christian C Carlos (Education Policy and Development, 2025)
As the maritime industry evolves in the Fourth Industrial Revolution (4IR), understanding the competencies and technological skills needed for Filipino maritime professionals is vital for addressing skills gaps and aligning emerging industry needs to maintain competitiveness in the global workforce. The study identified the core competencies and technological skills of maritime professionals in the 4IR, informing a strategic plan. A descriptive comparative-correlational research design was employed, covering 121 maritime professionals from MHEIs, shipping companies, and training centers. Snowball sampling was utilized to efficiently access deck and engine officers. The statistical tools used in treating the data were: frequency and percentage distribution for demographic profiles, weighted arithmetic means for core competencies and technological skills assessments, and Pearson correlation coefficients to explore relationships between competencies and technological skills. The Kruskal-Wallis H test was used to assess the significant difference in respondents' core competencies and technological skills by profile. Findings of the study revealed that respondents demonstrated average to above-average proficiency in various technical and digital skills. The correlation analysis reveals strong positive relationships between various competencies and technological skills. Competencies in technical and cybersecurity were average; strengths were noted in innovation, adaptability, digital literacy, and regulatory compliance. Significant differences were found in specific technological skills, such as automation and robotics, indicating a need for targeted training in advanced technologies. The findings underscore the importance of aligning specialized training with emerging industry demands. Likewise, fostering a culture of innovation and integrating continuous education opportunities is essential to address gaps in advanced technological skills.